Pacific Island countries case study - Dodds, E.H. (United Nations University TokyoJP, 2002)
Summarizes the findings of a study focusing on the situation of three small Pacific Island nations with regard to the negotiation, ratification, and implementation of a number of key multilateral environmental agreements.